Frankie gets a doggie - Huntington, Amy (Boyds Mills Press, an imprint of Boyds Mills & Kane, 2021)
Frankie and dad are going on an adventure--to the animal shelter! Frankie meets lots of doggies--big ones and shaggy ones, shy one and snuggly ones--but which dog should they choose? And what if Kitty is unhappy about this new family member? From furry nuzzels to belly tickles, this sweet, rhyming story is full of all the things that make dogs the perfect friends--most especially patience and love.